Antheroporum puudjaae (Millettieae: Fabaceae), a new species from Thailand - Mattapha, Sawai; Tetsana, Naiyana (Thai Forest Bulletin (Botany), 2021)
Antheroporum puudjaae, a new species discovered in Northern Thailand, is described and illustrated. It differs from other described species of Antheroporum by its drooping inflorescences and oblong fruits with 2–4 seeds. The generic description is expanded based on these new characters. An emended key to the species for the Flora of Thailand is also provided.